Patient preferences for treatment modalities for localised prostate cancer. Issue 2 (17th November 2022) - Teunissen, Frederik R.; Hehakaya, Charisma; Meijer, Richard P.; van Melick, Harm H. E.; Verkooijen, Helena M.; van der Voort van Zyp, Jochem R. N.
Abstract: Objectives: To assess the patient preferences and utility scores for the different conventional and innovative treatment modalities for localised prostate cancer (PCa). Subjects and Methods: Patients treated for localised PCa and healthy volunteers were invited to fill out a treatment‐outcome scenario questionnaire. Participants ranked six different treatments for localised PCa from most to least favourable, prior to information. In a next step, treatment procedures, toxicity, risk of biochemical recurrence and follow‐up regimen were comprehensibly described for each of the six treatments (i.e. treatment‐outcome scenarios), after which patients re‐ranked the six treatments. Additionally, participants gave a visual analogue scale (VAS) and time trade‐off (TTO) score for each scenario. Differences between utility scores were tested by Friedman tests with post hoc Wilcoxon signed‐rank tests. Results: Eighty patients and twenty‐nine healthy volunteers were included in the study. Before receiving treatment‐outcome scenario information, participants ranked magnetic resonance‐guided adaptive radiotherapy most often as their first choice (35%). After treatment information was received, active surveillance was most often ranked as the first choice (41%). Utility scores were significantly different between the six treatment‐outcome scenarios, and active surveillance, non‐ and minimal‐invasive treatments received higher scores. Conclusions: Active surveillance and non‐invasive treatment for localised PCa were the most preferred options by PCa patients and healthy volunteers and received among the highest utility scores. Treatment preferences change after treatment information is received.